IMPLEMENTASI PERATURAN BUPATI NOMOR 12 TAHUN 2014 TENTANG PEDOMAN PENGELOLAAN ALOKASI DANA KAMPUNG DI KABUPATEN KUTAI BARAT - Emma Paelongan; Aji Ratna Kusuma; Iman Surya (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to describe and analyze the implementation of the Financial Assistance To Kampung Dalam ADK Program as well as being inhibiting. The study concluded that the implementation of the ADK Policy relating to communications between actors in the implementation of ADK done through socialization conducted by a team of district to district level and consistency in the achievement of the message / command policy. But some things related to the communication/dissemination to the public about its policies ADK has not been done by the implementor. This resulted in the level of public understanding of the ADK to be not optimal in accordance with expectations. This condition will result in the difficulty of community participation in the implementation of the ADK and in monitoring activities.